1996
DOI: 10.1080/02786829608965396
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Deposition of Ultrafine Particles in Human Volunteers and Its Relationship to Airway Geometry

Abstract: ABSTRACT. Very large and very small particles most often deposit in the nasal airways. Human volunteers have often been used in deposition studies using particles > 0.5 pm, whereas physical airway models have been used in studies of ultrafine particle deposition. Studies in airway models provide large data sets with which to evaluate the deposition mechanism, while in vivo deposition data are needed to validate results obtained with nasal models. Four adult male, nonsmoking, healthy human volunteers (ages 36-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 17 publications
(30 reference statements)
7
50
1
1
Order By: Relevance
“…Results of the available in vitro experiments are in general agreement with the deposition data from in vivo studies for ultrafine aerosols (Cheng et al, 1996a). Based on a collection of in vivo nasal deposition studies, Cheng et al (1996b) suggested a best-fit correlation for particle sizes less than 150 nm. Later, Cheng et al (2003) incorporated in vivo and in vitro nasal deposition data of ultrafine and micrometer particles to develop a correlation for particle sizes in the diffusional and the impaction deposition regimes.…”
supporting
confidence: 71%
“…Results of the available in vitro experiments are in general agreement with the deposition data from in vivo studies for ultrafine aerosols (Cheng et al, 1996a). Based on a collection of in vivo nasal deposition studies, Cheng et al (1996b) suggested a best-fit correlation for particle sizes less than 150 nm. Later, Cheng et al (2003) incorporated in vivo and in vitro nasal deposition data of ultrafine and micrometer particles to develop a correlation for particle sizes in the diffusional and the impaction deposition regimes.…”
supporting
confidence: 71%
“…We can see an acceptable agreement with these data. Figure 4 shows a significant scatter in the data of experiments conducted in vivo, with different people [12,13]. The lower values lie close enough to our curve.…”
Section: Comparison Of Calculation Results With Calculated and Experimentioning
confidence: 63%
“…Such studies have confirmed aerosol deposition in the respiratory tract is strongly influenced by aerosol size, aerosol charge distribution, and breathing pattern Blanchard and Willeke, 1983;Yu and Diu, 1983;Kim and Jaques, 2004;Kim and Hu, 2006;Ali et al, 2008;Park and Wexler, 2008) and lung morphometric parameters (Cheng et al, 1996;Hofmann et al, 1999). However, all these methods have limitations.…”
Section: Introductionmentioning
confidence: 99%